Grenzüberschreitende kommunale Zusammenarbeit - Storbeck, Daniel (Universitätsverlag Göttingen, 2016)
Municipal and regional cross-border cooperation has already been common practice for a long time. This is shown by numerous existing Euroregions along the German border. The particular feature of this kind of cooperation is the participation of local and regional authorities of different states, which are separated by a national border. The judicial challenge is to legally overcome the national boundary in order to transform a mere partnership into an effective cooperation. This treatise outlines the existing instruments to implement such cooperation for German municipal authorities within their sphere of jurisdiction. Several questions are discussed: Are local authorities entitled to enter a transnational contract and if so, to what extent? What possibilities are offered by the German Constitution and existing umbrella agreements, and what is the relevance of the achievement of the European Regulation on a European Grouping of Territorial Cooperation? Furthermore, the important issue of transnational joint performance of exercising state authority as well as aspects of cross-border economic activities of local authorities are discussed.